Upaya Polisi Resort Kota Padang (Polresta Padang) dalam Menangani Balapan Liar di Kota Padang - Rizal Setiawan, Heru; Frinaldi, Aldri (Policy, Law and Political Research Center, 2023)
This study intends to determine the efforts of the Padang City Resort Police (Polresta Padang) in Dealing with Wild Races in the City of Padang. This research was carried out using qualitative methods with descriptive qualitative types. In determining the informants by using purposive sampling methods and techniques. Meanwhile, the data analysis technique used by the researcher is data reduction, then data presentation and verification and conclusion. The results showed that the efforts made by the Padang City Police Resort (Polresta Padang) in dealing with illegal racing in Padang City, can be said to have been effective in handling illegal racing that occurred in Padang City. This can be seen from the measurement indicators, namely preventive action, repressive and police administration indicators related to police management, namely operations/methods, supervision, and prosecution. As for the obstacles in the efforts of the Padang City Police Resort (Polresta Padang) in Dealing with Illegal Racing in the City of Padang, namely the lack of coordination received by the Padang City Police in an effort to deal with illegal racing and the lack of awareness of the public who report related illegal racing actions.